Risk Factors Increasing Vulnerability of Migrant Children - Miloshevska, Tanja; Frichand, Ana (Филозофски факултет, Скопје, 2018)
This article analyzes and highlights the major risk factors answerable for the exposure of migrant and refugee children to physical, psychological, and sexual violence and exploitation in the context of the ongoing migrant humanitarian crisis. This paper looks specifically at vulnerability to trafficking, abuse and exploitation, and the ways that particular migration contexts associated with irregular migration across the Western Balkan Route can affect risk and protective factors. Precisely, we draw attention to the lengthy asylum process, long wait times, inadequate accommodation facilities for vulnerable children, inhumane living conditions, lack of security, ineffective humanitarian and insufficiently resourced child protection systems.
Keywords: risk factors, migration, vulnerability, children, violence